2018
DOI: 10.1007/978-1-4939-8814-3_25
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Proteomics Studies in Identifying Moonlighting Proteins

Abstract: Proteomics studies that characterize hundreds or thousands of proteins in parallel can play an important part in the identification of moonlighting proteins, proteins that perform two or more distinct and physiologically relevant biochemical or biophysical functions. Functional assays, including ligand binding assays, can find a surprising second function for a protein that was previously identified as performing a different function, for example, a DNA binding ability for an enzyme in amino acid metabolism. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Exposition of multiple moonlighting proteins on candidal cell surface has been demonstrated by many research group (Chaffin, 2008;Jeffery et al, 2019;Satala et al, 2021), but the mechanisms of non-classic transport of these cytoplasmic proteins to the cell surface remain mysterious. In this study we present data supporting a hypothesis that significant amounts of moonlighting proteins, such as Gpm1, occur at the infections foci in a fluid phase due to release from extracellular vesicles and/or cytoplasm leakage from damaged or dead cells, and subsequently adsorb on the surface of living cells and moonlight there as supplementary adhesins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposition of multiple moonlighting proteins on candidal cell surface has been demonstrated by many research group (Chaffin, 2008;Jeffery et al, 2019;Satala et al, 2021), but the mechanisms of non-classic transport of these cytoplasmic proteins to the cell surface remain mysterious. In this study we present data supporting a hypothesis that significant amounts of moonlighting proteins, such as Gpm1, occur at the infections foci in a fluid phase due to release from extracellular vesicles and/or cytoplasm leakage from damaged or dead cells, and subsequently adsorb on the surface of living cells and moonlight there as supplementary adhesins.…”
Section: Resultsmentioning
confidence: 99%
“…Many of them are multitasking proteins that perform major, evolutionarily conserved functions inside the cell, such as critical involvement in major metabolic pathways. Due to their additional roles, manifested once these proteins appear on the cell surface, they are also known as "moonlighting" proteins (Jeffery, 2003; Karkowska-Ku- leta & Kozik, 2014;Jeffery, 2019;Satala et al, 2020). The apparent adhesin functions of numerous moonlighting proteins on the cell surface of pathogenic microorganisms determine their contribution to microbial pathogenensis (for reviews see: Karkowska-Kuleta & Kozik, 2014;Satala et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is now known that non-classical protein pathway exists in bacteria, but the secretion process is still unknown [18]. Several proteins have been called moonlighting proteins since they show different functions [72,73]. Some of them have been described as secreted, such as DnaK, GroEL, or SodA [74].…”
Section: Exoproteins Subcellular Localisationmentioning
confidence: 99%
“…In addition, high levels of ribosomal proteins on the surface of bacteria are highly immunogenic in many immune processes and can effectively induce an immune response in the organism (Kurar and Splitter, 1997 ; Spence and Clark, 2000 ), making them important targets for current study on vaccine candidate antigens, such as Rbp L7/L12, which has been found on the surface of several Gram-positive bacteria (Rodríguez-Ortega et al, 2006 ; Severin et al, 2007 ; Tjalsma et al, 2008 ). However, whether these proteins are keeping their biological activity at the bacterial surface, or do “moonlighting”, i.e., acquiring another function when surface-exposed, remains still unclear (Jeffery, 2003 , 2014 , 2016 , 2019 ). So, the determination of the exact number of ribosomal proteins is important for the precise knowledge about the structure and function of ribosomes.…”
Section: Discussionmentioning
confidence: 99%